2021
DOI: 10.3389/fonc.2021.591823
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Surgery Type and Adjuvant Therapy for T1N0M0 Lung Large Cell Neuroendocrine Carcinoma

Abstract: BackgroundThe appropriate treatment strategy for T1N0M0 lung large cell neuroendocrine carcinoma (LCNEC) was not well illustrated. We evaluated the efficacy of different surgery types and adjuvant therapy on patients with T1N0M0 LCNEC.MethodsPatients diagnosed T1N0M0 LCNEC from 2004 to 2016 were identified in the surveillance, epidemiology, and end results (SEER) database. Clinical characteristics, treatment and survival data were collected. The efficacy of surgery type and adjuvant therapy stratified by tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In keeping with previous studies, we confirmed that LCNECs are often associated with the male sex (67% older age, median age 64 years) and smoker status (87%) [ 6 , 7 , 19 , 21 , 24 ]. However, in some other studies, a prevalence of females or non-smokers was reported [ 9 , 14 , 24 ]. Most patients reported non-specific symptoms, such as fever or chest and back pain, whereas cough and hemoptysis were only described in a few patients (18%), in line with previous data [ 1 , 32 ].…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In keeping with previous studies, we confirmed that LCNECs are often associated with the male sex (67% older age, median age 64 years) and smoker status (87%) [ 6 , 7 , 19 , 21 , 24 ]. However, in some other studies, a prevalence of females or non-smokers was reported [ 9 , 14 , 24 ]. Most patients reported non-specific symptoms, such as fever or chest and back pain, whereas cough and hemoptysis were only described in a few patients (18%), in line with previous data [ 1 , 32 ].…”
Section: Discussionmentioning
confidence: 97%
“…LCNEC is a rare subtype of lung cancer with a high relapse rate [ 31 ]. Due to its low frequency, data related to early-stage LCNEC derived only from a relatively low number of studies [ 6 , 7 , 9 , 14 , 15 , 16 , 19 ], which included heterogeneous cohorts of patients having also patients with advanced diseases or who did not undergo tumor resection, or with a diagnosis of combined-LCNEC at histopathological analysis. Studies including only early and locally advanced LCNEC after complete resection of the tumor are very few [ 21 , 22 , 23 , 24 ] and focused mostly on overall survival ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations